Incidence of severe acute renal failure in adults: results of a community based study. Issue 6876 (20th February 1993) - Feest, T G; Round, A; Hamad, S
Abstract : OBJECTIVE--To determine the age related incidence of severe acute renal failure in adults in two health districts in England. DESIGN--Prospective study of patients identified as having severe acute renal failure within a two year period; subsequent monitoring of outcome for a further two years. SETTING--Two health districts in Devon. SUBJECTS--Those adults in a population of 444, 971 who developed severe acute renal failure (serum creatinine concentration > 500 mumol/l) for the first time during two years, with subsequent fall of the serum creatinine concentration below the index value. MAIN OUTCOME MEASURES AND RESULTS--125 adults (140 per million total population yearly, 172 per million adults) developed severe acute renal failure, of whom 90 (72%) were over 70. Age related incidence rose from 17 per million yearly in adults under 50 to 949 per million yearly in the 80-89 age groups. In 31 patients (25%) the cause was prostatic disease, which was related to a good prognosis (84% (26) alive at three months). Overall survival was 54% (67) at three months and 34% (42) at two years and was not significantly age related. 18 per million total population yearly (22 per million adult population) received acute dialysis. Referral rate for specialised opinion was 51 per million total population yearly with an estimated appropriate referral rate of 70 per million per year. CONCLUSIONS--The incidence of severe acute renal failure in the community is at least twice as high as the incidence reported from renal unit based studies. Prostatic disease, a preventable and treatable problem, is the most common cause. Survival figures indicate that age alone should not be a bar to specialist referral or treatment.